Pengaruh Pupuk Organik Cair Vermikompos dan Jenis Benih terhadap Efisiensi Penyemaian - Ramadhan, Igo; khair, Hadriman; Pillai, Sashikala Maruthai (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2024)
Liquid Organic Fertilizer (LOF) obtained of vermicomposting processis an alternative organic fertilizer that has the potential to enhance sustainable plant growth. This study aims to investigate the effects of liquid organic fertilizer vermicompost on the vegetative growth of selected lfruity plant species, as okra (Abelmoschus esculentus) eggplant (Solanum melongena), and white radish (Raphanus sativus). The research was conducted at the Integrated Organic Farm and the Organic Laboratory of the Malaysian Agriculture Research and Development Institute (MARDI) in Serdang, Selangor, Malaysia, during September 2024. The study was carried out in two phases: field trials and laboratory tests. The field trial used a non-factorial Randomized Block Design (RBD) with four treatments, each replicated three times. The treatments of LOF vermicompost were as follows: V1 = 25% LOF; V2 = 50% LOF; V3 = 75% LOF; and V4 = 100% LOF. The laboratory tests utilized a non-factorial Completely Randomized Design (CRD) with eleven treatments, also replicated three times. The treatments were: V0 = Control (no treatment); V1 = 10% LOF; V2 = 20% LOF; V3 = 30% LOF; V4 = 40% LOF; V5 = 50% LOF; V6 = 60% LOF; V7 = 70% LOF; V8 = 80% LOF; V9 = 90% LOF; V10 = 100% LOF. The results indicated that the concentration of liquid organic fertilizer (LOF) vermicompost did not significantly affect the time of plumule emergence, the number of leaves, the fresh weight, and the dry weight in okra, eggplant, and radish. However, a significant effect was observed on plant height growth in the seedling trays. The study showed no significant differences in responses to the concentrations of LOF vermicompost among the three seed types. Nonetheless, white radish (R. sativus) exhibited better growth potential, particularly in plant height in the seedling trays. The concentration of LOF vermicompost did not significantly influence the time of plumule emergence, the number of leaves, and the dry weight in okra, eggplant, and radish. However, significant effects were observed on plant height and fresh weight in the laboratory. Overall, radish (R. sativus) demonstrated the best potential compared to okra and eggplant, especially regarding plant height and fresh weight in the laboratory.